Level of Knowledge, Attitude, and Practices of General Physicians in West Java, Indonesia on Middle Ear Inflammation - Aziza Salsabila; Lina Lasminingrum; Sally Mahdiani; Shinta Fitri Boesoirie; Bambang Purwanto (Faculty of Medicine Universitas Padjadjaran, 2022)
Background: The prevalence of middle ear inflammation in West Java is still relatively high. General practitioners are at the forefront who see and treat the patients directly; thus, the number of cases can be reduced by increasing the competence of general practitioners. This study aimed to determine the level of knowledge, attitude, and practices of general practitioners in West Java towards middle ear inflammation, as an evaluation for improving health services in the community.Methods: This research was a descriptive study with a questionnaire conducted in August–December 2021 conducted online with a probability sampling technique of at least 368 general practitioners in West Java. The level of knowledge, attitude, and practices were calculated using the Guttman scale. The data were presented as a frequency distribution.Results: The results showed that the majority of the general practitioners still had poor knowledge of middle ear inflammation (n=325; 84.6%) as well as the attitude (n=333; 86.7%) and the level of practice (n=340; 88.5%).Conclusions: The level of knowledge, attitude, and practices of general practitioners in West Java towards middle ear inflammation is poor. Special interventions and approaches are needed to improve the competence of general practitioners in West Java based on the Standard Competency of Indonesian Doctors.